IMPLEMENTATION OF A WEB-BASED DIGITAL TOURISM INFORMATION SYSTEM AT THE DEPARTMENT OF YOUTH, SPORTS, AND TOURISM (DISPORAPAR) IN MOJOKERTO - Umaningrum, Cahyani; Rodiyah, Isnaini (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The research aims to analyze how the TIC system contributes to enhancing destination attractiveness and supporting regional tourism development through digitalization. Method: A descriptive qualitative approach was applied, with data collected through in-depth interviews, observation, and document analysis. The analysis was guided by George C. Edwards III’s policy implementation theory, focusing on four variables: communication, resources, disposition of implementers, and bureaucratic structure. Results: The findings reveal that the Web TIC implementation remains suboptimal, hindered by weak internal communication, limited IT resources and funding, low implementer motivation, and rigid bureaucratic processes that delay decision-making. Despite these challenges, the system demonstrates potential as a tool for improving accessibility to tourism information. Novelty: This study contributes by applying a policy implementation framework to assess digital tourism innovation at the regional level, emphasizing the need for structured communication, human resource development, dedicated budgets, and cross-sector collaboration to ensure effective and sustainable digital tourism information management.